Was Earth’s Water Acquired Locally during the Earliest Phases of the Solar System Formation? - Lise Boitard-Crépeau; Cecilia Ceccarelli; Pierre Beck; Lionel Vacher; Piero Ugliengo (The Astrophysical Journal Letters, 2025)
The origin of the terrestrial water remains debated, as standard solar system formation models suggest that Earth formed from dry grains, inside the snowline of the protosolar nebula (PSN). Here, we revisit this issue through the lens of computational chemistry. While the classically used snowline relies on a single condensation temperature, recent work in quantum chemistry shows that the binding energy (BE) of water on icy grains has a Gaussian distribution, which implies a gradual sublimation of water rather than a sharp transition. We use the computed distribution of BEs to estimate the radial distribution of adsorbed ice on the dust grains across the PSN protoplanetary disk. Our model reproduces the full range of estimated water abundances on Earth and matches the hydration trends observed in chondrite groups at their predicted formation distances. Thus, we suggest that a significant fraction of Earth’s water may have been acquired locally at early stages of the solar system formation, without requiring delivery from beyond the classical snowline.